2017
DOI: 10.1002/jcp.25728
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis and MicroRNA Expression Profiling Identified Seven miRNAs Associated With Progression of Oral Squamous Cell Carcinoma

Abstract: MicroRNAs have been used as diagnostic and prognostic biomarkers for many cancers including oral squamous cell carcinoma (OSCC). Several studies have been shown that microRNA (miRNA) play important roles during the progression of OSCC. However, the results vary largely in different studies due to different platforms and sample sizes. In this study, we systematically evaluated a large scale of miRNA profiles from current qualified OSCC samples, and further investigated the functions of genes regulated by these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 35 publications
1
17
0
1
Order By: Relevance
“…Our results regarding mir-21 , mir-31 , mir-133 , and mir-139 deregulation in oral cancer are in line with findings reported in a recently published meta-analysis ( 21 ). Existing non-overlapping miRNAs between that and our study can be explained with more rigorous criteria applied in the selection process of our study.…”
Section: Discussionsupporting
confidence: 93%
“…Our results regarding mir-21 , mir-31 , mir-133 , and mir-139 deregulation in oral cancer are in line with findings reported in a recently published meta-analysis ( 21 ). Existing non-overlapping miRNAs between that and our study can be explained with more rigorous criteria applied in the selection process of our study.…”
Section: Discussionsupporting
confidence: 93%
“…The combination of miR-133a and FOBT could be a potential detection mode in colorectal cancer screening [83]. Based on the information from The Cancer Genome Atlas (TCGA) database and Metaanalysis results, along with bioinformatics analysis, miR-133a was recognized as a potential biomarker of NSCLC [84][85][86], oral cancer [87,88], osteosarcoma [89], cervical cancer [90], prostate cancer [91], digestive tumors [92] including EC [93][94][95], GC [96,97], pancreatic ductal adenocarcinoma (PDAC) [98] and CRC [99]. A study of 8006 tumors including 19 tumor types suggested that hypoxia contributed to genomic instability.…”
Section: Mir-133a As a Potential Biomarkermentioning
confidence: 99%
“…In addition, miR‐125b can play tumor suppressive role and improve Cisplatin sensitivity in Osteosarcoma (Wang, Zhang, Wu, Zhang et al, ). Previous study has reported that miR‐125b is downregulated in OSCC by performing bioinformatics (Yan, Luo, Zhang, Li, & Liu, ). In our present study, we uncovered that miR‐125b was significantly decreased in OSCC cells and can be sponged by MALAT1.…”
Section: Introductionmentioning
confidence: 99%